PENGARUH KOMPLEKSITAS TUGAS, KOMITMEN PROFESIONAL DAN TEKANAN ANGGARAN WAKTU TERHADAP PERILAKU DISFUNGSIONAL AUDITOR” (STUDI EMPRISIS DI KANTOR BPKP PERWAKILAN PROVINSI MALUKU) - Limba, Franco Benony; Atarwaman, Rita; Hetharie, Chelsea (Jurnal Manajemen, Akuntansi, Ekonomi, 2023)
The aim of this study was to examine the effect of auditor's dysfunctional behavior is caused by task complexity, professional commitment, and time budget pressure. The location of this study is the BPKP Representative of Maluku Province. The population in this study were all Auditor Functional Officers who worked as the BPKP representatives of Maluku Province. The sample of this study was conducted by saturation sampling techniques. The data used are primary data with data collection techniques, namely questionnaires. The data analysis method used in this study is multiple linear regression analysis. Based on the results of the research, it is known that task complexity and professional commitment have a positive effect on the auditor's dysfunctional behavior. In contrast, time budget pressure has not to effect on the auditor's dysfunctional behavior.